Impact of Implementing Ex-Foreign Ship Moratorium Policy on Tuna Fishing Business in Benoa, Bali - I Ketut Wija Negara; Pande Gde Sasmita Julyantoro; Endang Wulandari Suryaningtyas; Made Ayu Pratiwi; Salman Mokoginta; Nu'man Najib; John Lynham (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
Regulation of the Minister of Maritime Affairs and Fisheries number 56 of 2014 and Regulation of the Minister of Maritime Affairs and Fisheries number 10 of 2015 help realize responsible fisheries management and combat Illegal, Unreported, and Unregulated (IUU) Fishing in Fisheries Management Area of ​​the Republic of Indonesia (WPP NRI). The policy of temporarily stopping permits (moratorium) for ships manufactured overseas (ex-foreign vessels) directly impacts fishermen working on ex-foreign vessels in the form of reduced income to loss of livelihoods. The research used a retrospective approach where policy analysis is carried out on the consequences of a policy after the policy is implemented. It is usually referred to as an evaluative analysis model, so it is expected to produce information that can improve the quality of the policies implemented by the government. The study aimed to determine the moratorium's impact on capture fisheries licensing on business activities, especially on fishing effort, catch per unit effort (CPUE), and socioeconomic conditions of fisheries at Benoa Harbor, Bali. This research was conducted from March to October 2022 in the Benoa Harbor Area, Bali. The data in this study were obtained from observation, interviews, questionnaires, and literature/document studies. The moratorium policy for ex-foreign vessels, followed by a ban on transshipment, significantly changed the pattern of trade, particularly for tuna, which was dominated initially by fresh tuna to frozen tuna with a lower value. The longline catches are dominated by Thunnus alalunga, followed by Thunnus maccoyii, Thunnus albacares, and Thunnus obesus. The total of ships in 2014 was 915 units, and only 246 ships remained in 2018. The significant decrease in fish landings in 2015-2017 is a real impact of the moratorium on ex-foreigners in Benoa. The results of the data analysis show that in 2014 the number of attempts was 2,264, which continued to decline until 2018, with only 697 trips.